Top 100 most influential manuscripts in erectile dysfunction. Issue 3 (August 2021) - Minto, Thomas; Bullock, Nicholas; Brown, Gareth
Erectile dysfunction (ED) is a common condition encountered by an array of subspecialists and is the most cited research topic within the field of andrology. This bibliometric analysis aims to identify the most influential papers that inform current clinical practice and likely shape future research. The Thompson Reuters Web of Science citation database was interrogated using search terms to cover the breadth of erectile dysfunction. Results were ranked according to citation number with country of origin, journal, topic, year of publication, author and institution also analysed. The search criteria matched 12, 570 manuscripts. The top 100 highest citation ranged from 3013 to 161 (median 229.5). The most cited manuscript reports the prevalence and risk factors of ED within the Massachusetts Male Aging Study. The most manuscripts were published by the Journal of Urology ( n = 15) with a total of 7913 citations. Institutions from the USA contributed the majority ( n = 55) with the UK ( n = 14) second. The most common theme represented was epidemiology ( n = 46) followed by treatment ( n = 27). This analysis provides a list of the most influential manuscripts within ED and illustrates what can be considered a 'highly citable' paper. The most influential papers in Erectile Dysfunction remain seminal works from the end of the last century. The most cited manuscript has been cited 194 times in the last 17 months showing its continued value. Only one paper published within the last decade has reached the top twenty exemplifying the relative lack of novel influential publications.